Ultrasonic image reconstruction based on maximum likelihood expectation maximization for concrete structural information. (August 2017) - Fan, Honghui; Zhu, Hongjin; Zhao, Xiaorong; Zhang, Jie; Wu, Dong; Han, Qingbang
Highlights: Concrete filled steel tube ultrasonic CT images are reconstructed based on MLEM. Ultrasonic time of flight data interpolation is used to reconstruct high quality image. Time of flight data normalization is proposed to reduce image artifacts. Steel tube position and general shape can be detected in the reconstruction image. Abstract: Many problems in measurement data are the physical quantities which are used to reconstruct an image for non-destructive testing. Time of flight data ultrasonic computed tomography is used in concrete non-destructive testing. Here the maximum likelihood expectation maximization (MLEM) algorithm and ultrasonic time of flight data is used to evaluate concrete filled steel tubes. When the image is reconstructed with the measurement data, the image shows many artifacts and therefor it is difficult to find useful information from the reconstruction image. To obtain a high quality image, time of flight data interpolation and normalization are proposed for image reconstruction system. Experimental results indicate the successful identification of the steel tube position and shape, which is not filled with concrete. The results imply that the time of flight data for ultrasonic computed tomography as an effective method of using the time of flight tomography to enhance the soundness of evaluation for concrete filled steel tubes. Graphical abstract: